Study on the related factors of TCM constitution and hemodynamics in patients with coronary heart disease - Mao, Boyan; Zhao, Zhou; Wei, Minghui; Liu, Xinzhu; Zhao, Ruoqi; Zhang, Weipeng; Duan, Mengyao (Frontiers in Cardiovascular Medicine, 2024)
Background: The concepts of "individualization" and "preventive treatment" should be incorporated into the precise diagnosis and treatment of coronary heart disease (CHD). Both hemodynamics and Chinese medicine constitution studies align with these two concepts. Methods: This study utilized data from 81 patients with CHD, including 12 patients with balanced constitution (BC), 20 patients with blood stasis constitution(BSC), 17 patients with phlegm-dampness constitution (PDC), 15 patients with qi-deficiency constitution (QDC), and 17 patients with other constitutions.Clinical data provided information on the patients' blood property, heart function, degree of coronary stenosis, coronary hemodynamics, and so on. These parameters